Liquidity transformation in asset management: Evidence from the cash holdings of mutual funds - Sergey Chernenko; Adi Sunderam (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
We study liquidity transformation in mutual funds using a novel data set on their cash holdings To provide investors with claims that are more liquid than the underlying assets, funds engage in substantial liquidity management. Specifically, they hold substantial amounts of cash, which they use to accommodate inflows and outflows rather than transacting in the underlying portfolio assets. This is particularly true for funds with illiquid assets and at times of low market liquidity. We provide evidence suggesting that mutual funds' cash holdings are not large enough to fully mitigate price impact externalities created by the liquidity transformation they engage in.
Keywords: G23; 330; liquidity transformation; asset management; mutual funds; cash holdings; fire sales